2022
DOI: 10.3390/pathogens11010061
|View full text |Cite
|
Sign up to set email alerts
|

The Bovine Tuberculoid Granuloma

Abstract: The bovine tuberculoid granuloma is the hallmark lesion of bovine tuberculosis (bTB) due to Mycobacterium bovis infection. The pathogenesis of bTB, and thereby the process of bovine tuberculoid granuloma development, involves the recruitment, activation, and maintenance of cells under the influence of antigen, cytokines and chemokines in affected lungs and regional lymph nodes. The granuloma is key to successful control of bTB by preventing pathogen dissemination through containment by cellular and fibrotic la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 117 publications
(238 reference statements)
2
23
1
Order By: Relevance
“…Histological examination confirmed the characteristic organization of tuberculous granulomas with central, partly calcified necrosis surrounded by an inflammatory cell infiltrate and a fibrous capsule. This is in accordance with the description of BCG-induced granulomas in goats [ 26 ] and tuberculous granulomas in goats [ 4 , 26 ], cattle [ 16 ] and humans [ 15 ]. Following the commonly used classification scheme for bovine tuberculosis [ 42 ], all granulomas were type 3 granulomas.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Histological examination confirmed the characteristic organization of tuberculous granulomas with central, partly calcified necrosis surrounded by an inflammatory cell infiltrate and a fibrous capsule. This is in accordance with the description of BCG-induced granulomas in goats [ 26 ] and tuberculous granulomas in goats [ 4 , 26 ], cattle [ 16 ] and humans [ 15 ]. Following the commonly used classification scheme for bovine tuberculosis [ 42 ], all granulomas were type 3 granulomas.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, subcutaneous vaccine granulomas in goats are a highly reproducible model for tuberculous granulomas. The complex organization of these dynamic structures reflects multiple interactions between mycobacteria, their target cells as well as non-specific and specific components of the host immune system [ 12 , 15 , 16 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study has also shown that in lions, there was greater upregulation of CXCL9 than either IFN-g or CXCL10 (Olivier et al, 2015). During M. bovis infection, IFN-g promotes cell-mediated immune responses by activating macrophages and granuloma formation (Silva Miranda et al, 2012;Palmer et al, 2022). Additionally, IFN-g, which is essential for the expression of CXCL9 and CXCL10 by macrophages and several cell types during the recruitment of T-cells at the site of infection, is produced to enhance host protection (Algood et al, 2003; TABLE 1 Results of mycobacterial culture confirmed Mycobacterium bovis infected and uninfected African lions using the QuantiFERON ® -TB Gold Plus (QFT) Mabtech Cat interferon gamma release assay (IGRA) and QFT CXCL9 gene expression assay (GEA).…”
Section: Discussionmentioning
confidence: 98%